Modeling Contextual Concerns in Enterprise Architecture - Antunes, G.; Barateiro, J.; Becker, C.; Borbinha, J.; Vieira, R. (2011 IEEE 15th International Enterprise Distributed Object Computing Conference Workshops, 2011)
Enterprise Architecture approaches are used to provide rigorous descriptions of the organization-wide environment, manage the alignment of deployed services to the organization's mission, end ensure a clear separation of the concerns addressed in an architecture. Thus, an effective Enterprise Architecture approach assists in the management of relations and dependencies of any components of the organization environment and supports the integration and evolution of the architecture. However, the quality of that approach is strongly influenced by the precision of the architecture context description, a fact which is not always recognized. This paper focuses on the architecture context description and addresses the gap between the stakeholders' concerns and the resulting architecture. Based on a combination of established references and standards, we show how an explicit integration of the architecture context into the architecture model improves the linking of concerns and key elements of the architecture vision. We apply our approach to a subject of increasing concern in the Information Systems area: longevity of information. Digital preservation is an interdisciplinary problem, but existent initiatives address it in a very domain-centric way, making it impossible to integrate documented knowledge into an overall organization architecture. We analyze several references and models and derive a description of the architecture context and a capability model that supports incremental development through an explicit distinction between systems and their capabilities. The presented approach allows not just any organization to assess their current digital preservation awareness and evolve their architectures to address this challenge, but in particular demonstrates the added value of an explicit architecture context model in an Enterprise Architecture approach.